Rahn As a Sharia Financial Instrument: A Literature Study on the Mechanism and Implications in Indonesia - Khafka Nafista Febrianty; Selvi (Takaza Innovatix Labs Ltd., 2025)
Despite the rapid development of Indonesia's Islamic financial system, rahn, as a sharia pawn instrument, faces challenges such as limited public understanding of the contract mechanism and competition with conventional pawnshops. This study aims to examine the operational mechanisms of rahn in Islamic financial institutions and their implications for financial inclusion. Using a descriptive qualitative approach through literature study, the population included rahn literature (2021-2025) with purposive sampling resulting in over 30 primary sources, including fatwas from the National Sharia Council (DSN-MUI) and regulations from the Financial Services Authority (OJK). The instruments consisted of primary texts (the Quran, hadith) and secondary texts (journals, reports), analyzed through thematic content analysis and validation of maqasid sharia. The results demonstrate the effectiveness of rahn through the riba-free qardh-ijarah contract, serving >60% of micro-enterprise customers while strengthening social solidarity. In conclusion, rahn strengthens ethical microfinance but requires regulatory standardization and digital innovation for broader reach